Reduced ambient PM2.5, better lung function, and decreased risk of chronic obstructive pulmonary disease. (November 2021) - Bo, Yacong; Chang, Ly-yun; Guo, Cui; Lin, Changqing; Lau, Alexis K.H.; Tam, Tony; Lao, Xiang Qian
Highlights: The PM2.5 levels in Taiwan peaked around 2004 and began to decrease since 2005. Improvements in ambient PM2.5 were associated with a better lung function. Reduced in ambient PM2.5 were associated with a decreased risk of COPD development. Abstract: Background: Several studies reported that long-term exposure to fine particulate matter (PM2.5 ) was associated with an increased risk of chronic obstructive pulmonary disease (COPD). It remains unclear whether reduced PM2.5 can decrease the risk of COPD development. Objective: To investigate the associations of dynamic changes (including deterioration and improvement) in long-term exposure to ambient PM2.5 with changes in lung function and the incidence of COPD. Methods: A total of 133, 119 adults (aged 18 years or older) were recruited in Taiwan between 2001 and 2014. All participants underwent at least two standard medical examinations including spirometry test. We estimated PM2.5 concentrations using a high-resolution (1 km 2 ) satellite-based spatio-temporal model. The change in PM2.5 (ΔPM2.5 ) was defined as the difference in concentration of PM2.5 between the respective visit and the previous visit. We used a multivariable mixed linear model and time-varying Cox model to investigate the associations of change in PM2.5 with annual change of lung function and the incidence of COPD, respectively. Result: The PM2.5 concentration in Taiwan increased during 2002–2004 and began to decrease around 2005. Every 5-µg/m 3 /year decrease in the annual change of PM2.5 (i.e., ΔPM2.5 /year of 5 µg/m 3 /year) was associated with an average increase of 19.93 mL/year (95 %CI: 17.42, 22.43) in forced expiratory volume in 1 s (FEV1 ), 12.76 mL/year (95 %CI: 9.84, 15.66) in forced vital capacity (FVC), 70.22 mL/s/year (95 %CI: 64.69, 76.16) in midexpiratory flow between 25 and 75% of the forced vital capacity (MEF25-75), 0.27%/year (95 %CI: 0.21%, 0.32%) in FEV1 /FVC/year. Every 5 µg/m 3 decrease in PM2.5 (i.e., ΔPM2.5 of 5 µg/m 3 ) was associated with a 12% (95 %CI: 7%, 17%) reduced risk of COPD development. The stratified and sensitivity analyses generally yielded similar results. Conclusion: An improvement in PM2.5 pollution exposure was associated with an attenuated decline in lung function parameters of FEV1, FVC, MEF25-75, and FEV1 /FVC, and a decreased risk of COPD development. Our findings suggest that strategies aimed at reducing air pollution may effectively combat the risk of COPD development.